Dilema Buruh Konstruksi Menuju Sejahtera: Studi Pekerja Muda di Kota Malang - Nanda Harda Pratama Meiji; Iin Ningtias; Nadya Bherta Viana Putri (Society, 2022)
One essential thing is examining labor welfare aspects, especially for young workers with a long future journey. During difficulties and limitations in finding work, youth with social capital and experience in the field try to become construction laborers. Their transition did not appear to be as smooth as one might imagine, even though they entered jobs that required “muscle” or physical. This study uses qualitative methods using observation and in-depth interviews with informants in the field. While searching for data, several young people explained their transition process in their dreams of achieving better welfare than today. The fluctuating transitional phase does not seem to reach their ideas to work and their dream phase. The risk of global employment in the context of their future as laborers swaying around will encourage them to get a better life.